Response of rice cultivars to liming in cerrado soil - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2014)
The different response of 100 rice (Oryza sativa L.) cultivars to liming was assessed in a greenhouse experiment using a Dark-Red-Latosol. A calibration curve was developed using different lime levels to get a range of Ca + Mg in the soil. With the help of this calibration curve, three levels of lime were applied (0, 10, 30 g per pot) corresponding to 0.6, 2.5 and 4.9 meq/100 g of Ca + Mg in the soil. Rice cultivars responded to lime application but response varied from cultivar to cultivar. The average response of 100 cultivars was determined. An increase of 23% in grain production was obtained at 30 g lime per pot as compared with no lime treatment. Yield increase for each cultivar was also calculated at 10 and 30 g lime treatments in relation to production at no lime. Based on this yield increase, cultivars were classified in three groups as low, medium and highly responsive to application of calcium and magnesium in the soil. Effect of lime on chemical properties of soil is discussed.